Factors affecting the adoption of Fin-tech in Pakistan based on the Unified Theory of Acceptance and Use of Technology Model: An empirical study on financial inclusion in Pakistan - Ashraf , Muhammad; Hafeez, Rana; Sajid, Abdul Nafay (Journal of Financial Technologies (Fintech), Inclusion and Sustainability, 2022)
Pakistan has seen a rise in financial technology (Fin-Tech) and mobile device use. The financial sector and entrepreneurs see Fin-Tech as a method to extend business potential, but mobile apps and other digital platforms must be established to explore these possibilities. Mobile app security concerns have skyrocketed, causing issues for users and Fin-Tech innovators. This article empirically explores how Fin-Tech adoption affects users' and organizations' expectations of effort, performance, social impact, facilitating conditions, behavioural intents, and adoption. This paper presents a UTAUT-based model for fin-tech adoption intention. This study examined 518 Bahawalpur residents and workers. Consultant-created online and paper questionnaires covered the study's objectives. Hence, fin-tech adoption is valuable for both the general public and its users. Independent variables moderated behavioural intention and Fin-Tech adoption. Bahawalpur companies and people adopting Fin-Tech can reduce productivity costs and save time. This research can help Bahawalpur residents adopt Fin-Tech.